2023
DOI: 10.1002/brb3.3102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of white matter alterations using diffusion kurtosis imaging in patients with amyotrophic lateral sclerosis

Abstract: Background To evaluate the degeneration of the corticospinal tract (CST) and corpus callosum (CC) in patients with motor neuron disease and upper motor neuron (UMN) dysfunction using diffusion kurtosis imaging (DKI). Methods Twenty‐seven patients and 33 healthy controls underwent magnetic resonance imaging along with clinical and neuropsychological testing. Tractography of diffusion tensor images was performed to extract tracts of the bilateral CST and CC. Group mean differences both across the entire averaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…The same trend emerged in previous studies of ALS that focused on the deep WM. 32,33 In the WM, increased RD and decreased RK have been correlated with demyelination and axonal loss in animal experiments, 58,59 and thus, our observations regarding the subcortical WM are in line with findings from postmortem studies of ALS. 20,56,60,61 We note, however, that DTI and DKI reflect the combined effects of multifaceted pathologies, some of which may act in opposite directions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The same trend emerged in previous studies of ALS that focused on the deep WM. 32,33 In the WM, increased RD and decreased RK have been correlated with demyelination and axonal loss in animal experiments, 58,59 and thus, our observations regarding the subcortical WM are in line with findings from postmortem studies of ALS. 20,56,60,61 We note, however, that DTI and DKI reflect the combined effects of multifaceted pathologies, some of which may act in opposite directions.…”
Section: Discussionsupporting
confidence: 88%
“…26,27 In addition, the community has not yet reached consensus on the appropriate model for GM. 25,28,29 Recent reports [30][31][32][33] have shown that DKI provides complementary information to DTI in terms of the ALS-related changes in both GM and WM. So far, DKI studies of the GM in ALS have adopted either ROI-based analyses 31 or voxel-based analyses with volumetric smoothing.…”
Section: Introductionmentioning
confidence: 99%